Vitamin D role in endothelial dysfunction development in patients with polycystic ovarian syndrome - T.L. Arkhypkina (Publishing House Zaslavsky, 2021)
Background. The study was aimed to determine the correlation between the blood concentration of vitamin D and factors that influence the function of the endothelium and the hemodynamic of gonads in women with polycystic ovary syndrome (PCOS). Material and methods. Sixty women aged from 18 to 26 years were examined: 30 women with a diagnosis of PCOS and 30 healthy women. The blood serum concentration of vitamin D, C-reactive protein (CRP), interleukin-6 (IL-6), homocysteine (Hcy), nitrites/nitrates (NOx), and arginine were investigated. Maximum systolic velocity (Vmax), resistance index (RI), and pulsatility index (PI) were measured with Doppler ultrasound. Cholecalciferol was used in a dose of 4000 IU per day for 12 weeks for the correction of deficiency of vitamin D. Results. The patients with PCOS were found to have a lower (Р < 0.001) average vitamin D than healthy women. The reduction of vitamin D concentration was combined with an increase (P < 0.001) in the average concentration of NOx and a decrease in arginine. It was found a positive association between vitamin D and arginine (r = 0.391; P < 0.05), between NOx and CRP (r = 0.432; P < 0.02), IL-6 (r = 0.476; P < 0.01), Vmax (r = 0.383; P < 0.05), RI (r = 0.369; P < 0.05), PI (r = 0.380; P < 0.05) and reverse correlation with arginine (r = –0.375; P < 0.05). It was not found an association between NOx and vitamin D (r = 0.207; P > 0.05), Hcy (r = 0.176; P > 0.05); between vitamin D and Vmax (r = 0.231; P > 0.05), RI (r = 0.201; P > 0.05), PI (r = 0.181; P > 0.05). The therapy of cholecalciferol level was accompanied by an increase (P < 0.001) in concentrations of vitamin D, arginine (P < 0.05) and a decrease in NOx (P < 0.02), IL-6 (P < 0.05), SRP (P < 0.001), Hcy (P < 0.001), Vmax (P < 0.001), RI (P < 0.001), PI (P < 0.01), quantity of antral follicles (P < 0.001), and the growth of follicles (P < 0.001). However, none of the studied indicators reached the indicators in healthy women. Conclusions. The deficiency of vitamin D is associated with increased markers of chronic inflammation, homocysteine, nitrate/nitrites, reduced concentration of arginine that provokes the development of endothelium dysfunction and, therefore, the hemodynamics disorders and folliculogenesis in the ovary.